Molecular Characterization of Plant Growth Promoting Pseudomonas from Rhizosphere of Euphorbia caducifolia Haines - Joshi, Bhavesh M.; Patel, Mrugesh M.; Parmar, Rudra B.; Singh, N. K.; Tapre, P. V. (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted during kharif 2020 at the Department of Microbiology, Chimanbhai Patel College of Agriculture, S. D. Agricultural University for molecular characterization of plant growth promoting Pseudomonas isolates from rhizosphere of Euphorbia caducifolia. Twenty Pseudomonas isolates (designated as PsEc1 to PsEc20) were axenically isolated from rhizospheric soil sample of Euphorbia caducifolia using Pseudomonas Isolation Agar Base (a selective medium). These isolates were tested gram negative, rod shaped, and oxidase positive. All 20 isolates were positive for utilization of maltose, esculin, citrate and malonate whereas these isolates showed varied results for utilization of xylose, fructose, galactose, sucrose and sorbitol. 16Sr DNA sequencing data revealed similarity of the isolates to different species of Pseudomonas, i.e., P. fluroscens (11), P. aeruginosa (3), P. putida (3), P. stutzeri (2) and P. syringe (1). These nucleotide sequences were submitted to the NCBI GenBank database with accession numbers respectively MT775484 to MT775503. The 16S rDNA sequences were aligned and used to reconstruct a phylogenetic tree with bootstrap values using software MEGA 6.06. The phylogenetic tree comprised of three clades. Clade I comprised of sixteen isolates, clade II four isolates and clade III only one isolate. The members of clade I belonged to P. fluorescens, P. putida and P. stutzeri whereas members of clade II comprised of P. aeruginosa. However, clade III consisted of P. syringae. In vitro test showed PsEc17 (P. fluorescens, MT775500) as most efficient in solubilizing tricalcium phosphate (78.53 µg ml–1) and IAA production (78.53 µg ml–1). PsEc17 also proved most efficient and showed 69.5 per cent inhibition of Fusarium oxysporum f. sp. cumini.